Synthesis, characterization and catalytic evaluation of cobalt and niobium oxide solids modified with alkaline earth metals - Pinheiro Sena, Maiana (2020)
Cobalt and niobium oxide solids modified with alkaline earth metals (Mg, Ca, and Sr) were synthesized and characterized to compare the second element effect on the catalyst structural and chemical properties. The materials were prepared by co-precipitation of cobalt nitrate and niobium oxalate solutions using ammonium hydroxide as precipitating agent. The samples were characterized by XRD, SEM, Ra-man, BET, TPR, ammonia TPD and cyclohexane dehydrogenation reaction (CHD). Results showed that Mg, Ca or Sr addition changed cobalt niobate crystalline structure, leading to alkaline earth metal nio-bates with lower crystallinity. It was observed that Mg, Ca or Sr increased the solids acidity and changed cobalt niobate reduction behavior so that the lowest amount of metallic cobalt was obtained when Mg was incorporated. Modifiers also decreased cobalt niobate dehydrogenation activity. This effect was higher with Mg or Sr addition.